Redash v5 quick start guide : create and share interactive dashboards using Redash - Leibzon, Alexander; Leibzon, Yael (Packt Publishing Ltd., 2018)
Learn how to quickly generate business intelligence, insights and create interactive dashboards for digital storytelling through various data sources with Redash Key Features Learn the best use of visualizations to build powerful interactive dashboards Create and share visualizations and data in your organization Work with different complexities of data from different data sources Book Description Data exploration and visualization is vital to Business Intelligence, the backbone of almost every enterprise or organization. Redash is a querying and visualization tool developed to simplify how marketing and business development departments are exposed to data. If you want to learn to create interactive dashboards with Redash, explore different visualizations, and share the insights with your peers, then this is the ideal book for you. The book starts with essential Business Intelligence concepts that are at the heart of data visualizations. You will learn how to find your way round Redash and its rich array of data visualization options for building interactive dashboards. You will learn how to create data storytelling and share these with peers. You will see how to connect to different data sources to process complex data, and then visualize this data to reveal valuable insights. By the end of this book, you will be confident with the Redash dashboarding tool to provide insight and communicate data storytelling. What you will learn Install Redash and troubleshoot installation errors Manage user roles and permissions Fetch data from various data sources Visualize and present data with Redash Create active alerts based on your data Understand Redash administration and customization Export, share and recount stories with Redash visualizations Interact programmatically with Redash through the Redash API Who this book is for This book is intended for Data Analysts, BI professionals and Data Developers, but can be useful to anyone who has a basic knowledge of SQL and a creative mind. Familiarity with basic BI concepts will be helpful, but no knowledge of Redash is required.